Discontinuation of long-acting reversible contraceptive methods and associated factors among reproductive-age women in Shashemene town, Oromia, Ethiopia - Fikru Letose; Alemtsehay Tusa; Degemu Sahlu; Yohannis Miherite (Frontiers Media S.A., 2024)
BackgroundThe early termination of long-acting reversible contraceptives (LARCs) raises issues for the healthcare system and has the potential to affect public health. Long-acting reversible contraception has now become more widely available and used, although a sizable percentage of women still do not use it. Therefore, this study aims to assess the factors associated with the discontinuation of the LARC method among female users of health facilities in Shashemene town in Oromia, Ethiopia.MethodsA facility-based cross-sectional study was conducted in Shashemene town involving 410 study participants from nine facilities. The study participants were selected by using a systematic sampling method. The data were collected by using structured interviewer-administered questionnaires, entered into EpiData version 4.6.0.2, and exported to SPSS version 25 for analysis. Bivariate and multivariable logistic regressions were used to examine the association between independent variables and LARC discontinuation. The results were presented using the odds ratio at 95% CI. p < 0.05 was used to indicate statistical significance.ResultThe overall prevalence of women who discontinued the LARC method before the due date was 57.2%. Having an occupation as a housewife, desire for pregnancy, unwarned side effects, effectiveness, and dissatisfaction with the service provided were the factors positively associated with the discontinuation of the contraception.ConclusionThe prevalence of the discontinuation of LARCs was high. Pre-insertion, effective counseling about the benefits, follow-up care, management of side effects, and client reassurance are recommended.